Comparative evaluation of different fungicides and bio-agents for management of spot blotch of barley caused by Bipolaris sorokiniana (Sace. Ex Sorok) - Khan, Javed Bahar; Katiyar, Sugam; Kanchan, Charul; Kumar, Jitendra; Gupta, Pravir Kumar (Journal of Cereal Research, 2021)
Among the fungicides Propiconazole, Tebuconazole, Azoxystrobin and Azxoxystrobin + Difenconazole completely inhibited the mycelia growth of pathogen at 200 ppm concentration under in-vitro condition. Among bio control agents, T. harzianum-1 (77.90 per cent) was found most effective antagonist against pathogen followed by T. harzianum-2 (74.80per cent) and T. viride-1 (74.41per cent).